An Experimental Model of Eosinophilic Chronic Rhinosinusitis Induced by Bacterial Toxins in Rabbits. Issue 6 (November 2019) - Braga, Andréa A.; Valera, Fabiana C. P.; Faria, Francesca M.; Rossato, Maria; Murashima, Adriana A. B.; Fantucci, Marina Z.; Aragon, Davi C.; Queiroz, Danielle L. C.; Anselmo-Lima, Wilma T.; Tamashiro, Edwin
Background: The pathophysiology of chronic rhinosinusitis (CRS) is still not well known due to the multifactorial etiologies involved. Bacteria play a role in the pathogenesis of CRS by various means, including biofilm adhesion, intracellular persistence, or inducing inflammation secondary to toxins. Endotoxins and exotoxins, especially Staphylococcus aureus superantigens, can produce significant immune responses in the host and are implicated in patients with CRS. The majority of animal models described for CRS revalidates the pathophysiology of acute sinusitis, ostium occlusion, or foreign body associated infection. Objectives: To evaluate an experimental model of eosinophilic CRS using prolonged exposure to bacterial toxins. The histological changes in rabbits exposed to S. aureus enterotoxin B (SEB), lipopolysaccharide (LPS), or lipoteichoic acid (LTA) were compared. Methods: After induction with ovalbumin (OVA) sensitization with subcutaneous injection for 2 weeks, rabbits underwent surgery to insert an indwelling catheter into the maxillary sinus. The sinus was irrigated with OVA 3 times weekly for 2 weeks, followed by sinus irrigation with bacterial toxin (SEB: 1 µg/mL, LPS: 100 ng/mL, or LTA: 100 ng/mL) 3 times weekly for 4 weeks. The histological changes in the treated sinus were compared with control rabbits. Results: Sinuses exposed to bacterial toxins (SEB, LPS, and LTA) produced significant mucosal thickening with infiltration of inflammatory cells, notably eosinophils. SEB was the only toxin that promoted a mixed pattern of inflammation, including eosinophilic and neutrophilic infiltration. Conclusion: Our experimental model of eosinophilic CRS in rabbits produced significant mucosal thickening and inflammation in the sinuses exposed to bacterial toxins, with histological changes analogous to what is observed in patients with CRS with nasal polyps. This model may serve as a basis for future investigation of the pathogenesis of eosinophilic CRS in relation to bacterial toxins or as a model for testing new therapeutic modalities for this disease.